2007
DOI: 10.1088/0951-7715/20/10/007
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behaviour of solutions of a free boundary problem modelling the growth of tumours in the presence of inhibitors

Abstract: We study a free boundary problem modelling the growth of non-necrotic tumours in the presence of external inhibitors. In the radially symmetric case this model was rigorously analysed by Cui (2002 J. Math. Biol. 44 395-426).In this paper we study the radially non-symmetric or non-radial case, so that the effect of internal pressure p has to be taken into account. The boundary condition for p is given by the equation p = γ κ, where κ is the mean curvature of the tumour surface and γ is a positive constant (surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…By and , we can easily show that γ k is monotone decreasing in inhibitor supply trueβ̄ (cf. Lemma 6.1 of . It implies that external inhibitors may also have positive effects in limiting the ability of tumor's invasion (see ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By and , we can easily show that γ k is monotone decreasing in inhibitor supply trueβ̄ (cf. Lemma 6.1 of . It implies that external inhibitors may also have positive effects in limiting the ability of tumor's invasion (see ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, msubnormallimkMathClass-rel→MathClass-rel∞γkMathClass-rel=0. If trueσ̄MathClass-bin−trueσ̃MathClass-bin−νtrueβ̄MathClass-rel<0 then there exists kMathClass-bin*MathClass-bin*MathClass-rel∈double-struckN such that for k > k * * , γ k < 0. If λ 2 > λ 1 + 1 ∕ ν and νtrueβ̄MathClass-rel<trueσ̄MathClass-rel<normalmin{}trueσ̃MathClass-bin+νtrueβ̄MathClass-punc,λ2trueσ̃MathClass-bin+trueβ̄λ2MathClass-bin−λ1, then for all k ≥ 2, γ k < 0. Proof Recall the well‐known formula of modified Bessel functions (cf. (4.25) of ) Ik(r)MathClass-rel=12πk()normaler2kk()1MathClass-bin+O()1k1emquadas2.56804pttmspace2.56804pttmspacekMathClass-rel→MathClass-rel∞MathClass-punc. It follows that IkMathClass-bin+32(r)IkMathClass-bin+12(r)MathClass-rel=normaler(2kMathClass-bin+1…”
Section: Linearization and Eigenvaluesmentioning
confidence: 96%
See 2 more Smart Citations
“…Later, for problem (1.1)-(1.7) in the absence of inhibitors (β = 0), Friedman and Lam [8] proved that, for any α > 0, 0 <σ <σ , there exists a unique radially symmetric solution σ * (r) with radius R * ; furthermore, Hu et al [10] showed that for each μ m (m ≥ 2), there exist symmetry-breaking solutions bifurcating from the radially symmetric solution. While, if the inhibitor is present (β = 0) and the boundary conditions (1.4) and (1.5) are replaced by the boundary conditions σ =σ , β =β (which is formally the case α = ∞, τ = ∞), the existence and asymptotic stability of radially symmetric solutions were studied in [17,25,26]. In the sequel, for each μ m (m > m * * ), Wang [11] established the existence of a sequence of symmetry-breaking solutions bifurcating from the radially symmetric solution.…”
Section: Introductionmentioning
confidence: 99%